1989
DOI: 10.1210/endo-124-1-7
|View full text |Cite
|
Sign up to set email alerts
|

The Aged Rat Model of Ovarian Hormone Deficiency Bone Loss*

Abstract: Three studies were carried out. First, the effects of aging on the maturation of the female skeleton were assessed. Second, the hypothesis that has linked ovarian hormone deficiency bone loss to hypercalcemic suppression of the parathyroids leading to a decrease in 1,25-dihydroxyvitamin D synthesis and gut absorption of calcium was examined. Third, the effects of ovariectomy and a combination of ovarian hormone deficiency and low dietary calcium on bone and the calcium-regulating hormones were evaluated. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
120
2
6

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(151 citation statements)
references
References 28 publications
15
120
2
6
Order By: Relevance
“…MK-4 has been shown to inhibit bone resorption in a mouse calvaria culture system (22) and en hance the mineralization of osteoblasts in a human cell culture system (23). It is well known that calcium absorp tion from the intestine decreases in ovariectomized rats (24) and in rats that have been treated with steroids (25). In this study, the reduction in calcium balance tended to induce the decrease in bone density, suggesting that cal cium balance plays an important role in bone metabo lism.…”
Section: Discussionmentioning
confidence: 50%
“…MK-4 has been shown to inhibit bone resorption in a mouse calvaria culture system (22) and en hance the mineralization of osteoblasts in a human cell culture system (23). It is well known that calcium absorp tion from the intestine decreases in ovariectomized rats (24) and in rats that have been treated with steroids (25). In this study, the reduction in calcium balance tended to induce the decrease in bone density, suggesting that cal cium balance plays an important role in bone metabo lism.…”
Section: Discussionmentioning
confidence: 50%
“…The present study therefore differed from our previous study (34) which showed a preventive effect of the combination of etidronate and 1a (OH)D 3 on bone loss starting 1 week after OVX in 14-week-old rats. In the present study we ovariectomized 40-week-old rats in whom bone growth and maturation have been completed (35,36), and treatment started 15 weeks after surgery. As a bisphosphonate, this study used alendronate, a more potent and prevalent bisphosphonate than etidronate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect shown in the previous study was not curative but preventive for bone loss by OVX, because the application of etidronate and /or 1a (OH)D3 started only one week after the operation. In addition, the rats used in the study were 14-week-old when bone growth and maturation had not yet been completed (35,36). To investigate the curative effect of the combined treatment with bisphosphonates and 1a (OH)D3 on established postmenopausal osteoporosis, in the present study we ovariectomized 40-week-old rats and the application of agents started 15 weeks after the surgery.…”
mentioning
confidence: 99%
“…Although the ovariectomized rat has been used frequently to demonstrate the loss of trabecular bone volume in the tibia, vertebra, and femur due to aging and estrogen depletion (15)(16)(17), only one study included the rat maxilla (18), and one other (19) included the rat mandible.…”
Section: Discussionmentioning
confidence: 99%